(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
Virtual Libraries serves the new or future generation users of the libraries. Virtual libraries are the new vision of libraries of the future. This paper provides an overview of a Virtual Library System and the benefit of implementing virtual reality (VR) or augmented reality (AR) usage. It also narrates purpose, features, functions, design and development of a Virtual Library and Virtual Library Environment.